2020
DOI: 10.3390/pathogens9110862
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Legionella pneumophila Populations by Multilocus Variable Number of Tandem Repeats (MLVA) Genotyping from Drinking Water and Biofilm in Hospitals from Different Regions of the West Bank

Abstract: The West Bank can be considered a high-risk area for Legionnaires’ disease (LD) due to its hot climate, intermittent water supply and roof storage of drinking water. Legionella, mostly L. pneumophila, are responsible for LD, a severe, community-acquired and nosocomial pneumonia. To date, no extensive assessment of Legionella spp and L. pneumophila using cultivation in combination with molecular approaches in the West Bank has been published. Two years of environmental surveillance of Legionella in water and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 83 publications
8
37
0
Order By: Relevance
“…This study included 60 L. pneumophila environmental strains isolated from eight hospitals in the West Bank, Palestine ( Table 1 and Supplementary Material Table S1 ). Genotyping was conducted using multilocus variable number of tandem repeat analysis using 13 loci—MLVA-13 (MLVA-12 plus 1 loci unique for the MLVA-8 scheme) designated as (MLVA-8(12) [ 38 , 45 ] assigning the majority of the strains to three genotypes (Gt4(17), Gt6(18), and Gt10(93)) and four clonal complexes (VACC1, VACC2, VACC5 and VACC11) [ 38 ]. Table 1 describes the details of the environmental L. pneumophila isolates used for this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study included 60 L. pneumophila environmental strains isolated from eight hospitals in the West Bank, Palestine ( Table 1 and Supplementary Material Table S1 ). Genotyping was conducted using multilocus variable number of tandem repeat analysis using 13 loci—MLVA-13 (MLVA-12 plus 1 loci unique for the MLVA-8 scheme) designated as (MLVA-8(12) [ 38 , 45 ] assigning the majority of the strains to three genotypes (Gt4(17), Gt6(18), and Gt10(93)) and four clonal complexes (VACC1, VACC2, VACC5 and VACC11) [ 38 ]. Table 1 describes the details of the environmental L. pneumophila isolates used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Multi locus variable number of tandem repeats (VNTR) analysis (MLVA) using 13 loci designated as MLVA-8(12) was successfully used to assess the genetic diversity among L. pneumophila isolates. VNTRs consist of relatively short DNA fragments repeated in tandem and can vary in copy number among strains [ 38 , 39 , 40 , 41 , 42 ]. Recent publications demonstrated that the majority of clinically relevant strains can be grouped into a limited number of Clonal Complexes (CCs) defined by MLVA, called VNTR analysis CC (VACC) [ 38 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations